Anti-Inflammatory Humulene-Type Sesquiterpenoids from Asteriscus Graveolens - Alorfi, Hajer S.; Aljohany, Fayza A.; Alamri, Fatima B.; Althagbi, Hanan I.; Abdel-Naim, Ashraf B.; Alarif, Walied M.; Budiyanto, Fitri; Aboubakr, Esam M. (Journal of Contemporary Medical Sciences, 2024)
Objectives: Inflammation is the initial physiological reaction of the immune system to infection or irritation, leading significant risk factors for several forms of cancer. The genus Asteriscus has been observed to possess a notable abundance of sesquiterpenes with anti-inflammatory properties. This study was designed to assess the anti-inflammatory activity of the sesquiterpenoids isolated from Asteriscus graveolens. Methods: The organic extract of the Asteraceae plant A. graveolens was subjected to different chromatographic and spectroscopic techniques for isolation, purification, and identification of sesquiterpenoid contents. The isolated compounds were screened for anti-inflammatory activities in two animal models: rat paw edema and rat ear edema. Histopathological examinations as well as biochemical markers of inflammation were assessed. This was followed by in silico screening for anti-inflammatory activity. Results: Four known sesquiterpenoids were isolated from A. graveolens, including two humulene derivatives, namely, 9-oxohumula-4-en-6,15-olide (1), and 9-oxohumula-1(10)(Z),4,7(E)-trien-6,15-olide (2) and two bisabolene derivatives, identified as bisabola-2,10-dien-1-one (3) and 6- hydroxybisabola-2,10-dien-1-one (4) described. In the rat paw edema model, compound 2 showed highest activity in preventing formation carrageenan-induced paw edema. This was confirmed by histopathological examinations that indicated partial preservation of the epidermal and dermal layers. Further, the compound significantly inhibited cyclooxygenase-2 (COX-2) and tumor necrosis factor-α (TNF-α) release. In the croton oil indued rat ear edema, compounds 2 and 4 significantly inhibited ear edema and protected against histopathological alterations. This was associated with prevention of myeloperoxidase (MPO) concentration in ear tissues. Molecular docking and molecular dynamic simulation indicated the affinity and docking stability of compounds 1-4 to the selected inflammatory protein. Conclusion: Phytochemical investigation of A. graveolens resulted in the isolation and characterization of four sesquiterpenes. In particular, compound 2 showed potent anti-inflammatory activity in carrageenan rat paw edema and croton oil ear edema.